99.5k views
5 votes
Please show to answer this

Please show to answer this-example-1

1 Answer

7 votes

Answer:


(q \circ r)(7)=22


(r \circ q)(7)=8

Explanation:

1st problem:


(q \circ r)(7)=q(r(7))

r(7) means to replace x in
√(x+9) with 7.


r(7)=√(7+9)=√(16)=4


(q \circ r)(7)=q(r(7))=q(4)

q(4) means replace x in
x^2+6 with 4.


q(4)=4^2+6=16+6=22.

Therefore,


(q \circ r)(7)=q(r(7))=q(4)=22

2nd problem:


(r \circ q)(7)=r(q(7))

q(7) means replace x in
x^2+6 with 7.


q(7)=7^2+6=49+6=55.

So now we have:


(r \circ q)(7)=r(q(7))=r(55).

r(55) means to replace x in
√(x+9) with 55.


r(55)=√(55+9)=√(64)=8

Therefore,


(r \circ q)(7)=r(q(7))=r(55)=8.

User Lincr
by
5.8k points